2018
DOI: 10.1017/s1742170518000170
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of residues from the invasive Acacia sp. for weed control

Abstract: A sustainable practice for weed control and crop protection is the incorporation of green manures with phytotoxic potential. It is gaining attention as a way to reduce the use of synthetic herbicides in agriculture and so pot experiments and field trials were conducted to explore the possible use of residues of Acacia species to alleviate weed emergence. We assessed, under greenhouse conditions, the herbicidal effect of phytotoxic manures from Acacia dealbata and Acacia longifolia applied to soil at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
(108 reference statements)
1
16
0
Order By: Relevance
“…The equivalent biomass quantity on a dry mass basis, composed of only flowers or flowering green branches, was able to produce similar phytotoxic effects, thus pointing out the potential of both species to produce and emit bioactive VOCs from the total aerial biomass. These results extend the interest of both shrub species as sources of natural products with bioherbicide potential, or to be used as bioherbicide green manures, as has been proposed for other allelopathic biomass-rich invasive species [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The equivalent biomass quantity on a dry mass basis, composed of only flowers or flowering green branches, was able to produce similar phytotoxic effects, thus pointing out the potential of both species to produce and emit bioactive VOCs from the total aerial biomass. These results extend the interest of both shrub species as sources of natural products with bioherbicide potential, or to be used as bioherbicide green manures, as has been proposed for other allelopathic biomass-rich invasive species [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 59%
“…However, they continue to be a largely untapped source of active compounds for potential use in agricultural fields. Interestingly, very recent approaches have proposed the use of allelopathic biomass from forest residues or invasive tree species as bioherbicide green manures [ 36 , 37 ]. Allelopathic biomass incorporated into the soil can release genuine ‘cocktails’ of allelochemicals that could control the germination and growth of different weed species.…”
Section: Introductionmentioning
confidence: 99%
“…Puig et al [14,15] have shown that the incorporation of Eucalyptus globulus leaves as a soil amendment inhibited the emergence of some common weeds of the maize, and notably reduced weed biomass throughout the whole growing period. Souza-Alonso et al [16], using residues from Acacia dealbata and A. longifolia incorporated into the soil, have observed some negative effects on dicotyledon weeds. These practices sum up the recycling of waste material from the agroecosystem, that is, allelopathic forest residues and invasive species, and their use in eco-friendly practices for plant protection.…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts, mulches, or green manures obtained from allelopathic/phytotoxic plant material could be used as a source of natural herbicides in agriculture . The potential herbicidal effect of green manures and mulches based on A. dealbata waste material has been recently assessed on accompanying weeds in maize crops . Despite not being as inhibitory as suspected, Acacia waste was useful in controling dicotyledonous weeds in modestly weed‐infested soils .…”
Section: Introductionmentioning
confidence: 98%
“…[29][30][31] The potential herbicidal effect of green manures and mulches based on A. dealbata waste material has been recently assessed on accompanying weeds in maize crops. 32 Despite not being as inhibitory as suspected, Acacia waste was useful in controling dicotyledonous weeds in modestly weed-infested soils. 32 On the other hand, methanol-soluble compounds extracted from A. dealbata bark improved the growth of Lactuca sativa under no-stress conditions, 28 suggesting a potential biostimulating effect.…”
Section: Introductionmentioning
confidence: 99%